2020
DOI: 10.1088/2053-1591/abbd0a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sc on laser hot-wire welding performance of 7075 aluminum alloy

Abstract: In order to clarify the effects of Sc modification on laser hot-wire welding performance of 7075 high strength aluminum alloys, the changing rules of weld formation, microstructure, element loss, mechanical performances and pores of weld joints were investigated during laser fusion welding, laser hot-wire welding and Sc-modified laser hot-wire welding. Comparing with laser fusion welding, the filler wire in laser hot-wire welding brought welding material and hot wire energy, resulting in better weld formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For example, in the case of high-strength aluminum alloy represented by the 7xxx series, some studies have shown that the joint strength is only 50% to 65% of the base metal when joined by traditional fusion welding methods [40,41]. Even with laser welding, electron beam welding, laser-arc hybrid welding, etc., the joint strength can only reach ~79% [10,42,43]. The plastic deformation in the weld zone, such as rolling, can increase the joint strength by about 24% [44].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of high-strength aluminum alloy represented by the 7xxx series, some studies have shown that the joint strength is only 50% to 65% of the base metal when joined by traditional fusion welding methods [40,41]. Even with laser welding, electron beam welding, laser-arc hybrid welding, etc., the joint strength can only reach ~79% [10,42,43]. The plastic deformation in the weld zone, such as rolling, can increase the joint strength by about 24% [44].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many factors affecting welding behavior, the structure of the pre-welding member [ 13 ], parameters of welding [ 14 ], selection of a heat source [ 15 ], welding methods and optimization [ 16 ] and the treatment method after welding [ 17 , 18 ], affect the quality of welding, the service life of a component and the safe operation of it. These factors are the guarantee of a high-performance weld and good mechanical properties [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%